2014
DOI: 10.1093/neuonc/nou164
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR signaling pathway as a treatment target for intracranial neoplasms

Abstract: Inhibition of the mammalian target of rapamycin (mTOR) signaling pathway has become an attractive target for human cancer therapy. Hyperactivation of mTOR has been reported in both sporadic and syndromic (hereditary) brain tumors. In contrast to the large number of successful clinical trials employing mTOR inhibitors in different types of epithelial neoplasms, their use to treat intracranial neoplasms is more limited. In this review, we summarize the role of mTOR activation in brain tumor pathogenesis and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 151 publications
2
36
0
Order By: Relevance
“…Rapamycin is an allosteric inhibitor of mTOR, which has been shown to dramatically reduce the self-renewal and tumorigenic activity of glioma cells and GSCs ( 53 ). In agreement with these results, several phase I and II clinical trials, with some of its rapalogs, such as everolimus or temsirolimus, alone or in combination, showed radiographic and symptomatic evidence of improvement in delaying tumor progression without provoking high toxicity in patients with newly diagnosed or recurrent glioblastoma ( 54 ). It has recently been demonstrated that mTOR regulates the expression of SOX2.…”
Section: Therapeutic Approaches Toward Sox2 Reduction In Gbmsupporting
confidence: 57%
“…Rapamycin is an allosteric inhibitor of mTOR, which has been shown to dramatically reduce the self-renewal and tumorigenic activity of glioma cells and GSCs ( 53 ). In agreement with these results, several phase I and II clinical trials, with some of its rapalogs, such as everolimus or temsirolimus, alone or in combination, showed radiographic and symptomatic evidence of improvement in delaying tumor progression without provoking high toxicity in patients with newly diagnosed or recurrent glioblastoma ( 54 ). It has recently been demonstrated that mTOR regulates the expression of SOX2.…”
Section: Therapeutic Approaches Toward Sox2 Reduction In Gbmsupporting
confidence: 57%
“…The protein codified by this gene shows similarity with NOTCH2 [29], so it is possible that neural tube defects might be caused also by mutations in other genes coding for proteins that belong to the Notch signaling pathway. This mechanism had been already described in many other genetic conditions such as Rasopathies [30], coesinopathy [31], and mTOR related conditions [32]. Consequently, other genes associated with neural tube defects [11], including spina bifida, were sequenced, with negative results.…”
Section: Discussionmentioning
confidence: 91%
“…There are approximately twenty current clinical studies using mTOR inhibitors for the treatment of gliomas [ 55 ]. However, phase II studies with recurrent glioblastoma reported no efficacy of TEM in the combination with TMZ, sorafenib, bevacizumab, or erlotinib [ 55 ]. Although we used a clinically relevant TEM concentration [ 56 ], the discrepancy between cell culture responses (Fig.…”
Section: Discussionmentioning
confidence: 99%